2021
DOI: 10.1590/fst.33819
|View full text |Cite
|
Sign up to set email alerts
|

Cashew nut-based beverage: development, characteristics and stability during refrigerated storage

Abstract: A cashew nut-based beverage was obtained using broken cashew kernels and its composition and stability were evaluated during refrigerated storage for 60 days. Sensory tests were performed to define the formulation, testing the best proportion between kernels and water, the effect of kernel roasting, the ideal sweetness, the beverage attributes and the sensory acceptance. A cashew nut beverage can be obtained by grinding the kernel with water in the proportion of 1:10 (m/m) with added sugar at 3%, followed by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…A total of 32 studies were selected according to the inclusion and exclusion criteria. The studies were conducted in 13 different countries: Brazil (59.38%; n = 19) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]; India (6.25%; n = 2) [ 49 , 50 ]; Argentina (3.13%; n = 1) [ 51 ]; Belgium (3.13%; n = 1) [ 52 ]; Canada (3.13%; n = 1) [ 23 ]; Denmark (3.13%; n = 1) [ 53 ]; Germany (3.13%; n = 1) [ 54 ]; Ghana (3.13%; n = 1) [ 55 ]; Iran (3.13%; n = 1) [ 56 ]; Ireland (3.13%; n = 1) [ 57 ]; Nigeria (3.13%; n = 1) [ 58 ]; Pakistan (3.13%; n = 1) [ 59 ]; Turkey (3.13%; n = 1) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 32 studies were selected according to the inclusion and exclusion criteria. The studies were conducted in 13 different countries: Brazil (59.38%; n = 19) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]; India (6.25%; n = 2) [ 49 , 50 ]; Argentina (3.13%; n = 1) [ 51 ]; Belgium (3.13%; n = 1) [ 52 ]; Canada (3.13%; n = 1) [ 23 ]; Denmark (3.13%; n = 1) [ 53 ]; Germany (3.13%; n = 1) [ 54 ]; Ghana (3.13%; n = 1) [ 55 ]; Iran (3.13%; n = 1) [ 56 ]; Ireland (3.13%; n = 1) [ 57 ]; Nigeria (3.13%; n = 1) [ 58 ]; Pakistan (3.13%; n = 1) [ 59 ]; Turkey (3.13%; n = 1) [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 36.36% ( n = 8) of the matrices belong to the group of nuts that constituted 41.80% ( n = 51) of beverages: almond ( Prunus dulcis ) (9.84%, n = 12) [ 23 , 36 , 52 , 53 , 54 , 57 , 58 ]; sapucaia nut ( Lecythis pisonis ) (9.02%, n = 11) [ 47 ]; cashew nut ( Anacardium occidentale ) (6.56%, n = 8) [ 23 , 32 , 33 , 52 , 54 , 57 , 59 ]; coconut ( Cocos nucifera ) (6.56%, n = 8) [ 23 , 52 , 53 , 54 , 57 ]; hazelnut ( Corylus avellana ) (3.28%, n = 4) [ 53 , 54 , 57 ]; cupuaçu almond ( Theobroma grandiflorum ) (2.46%, n = 3) [ 35 ]; tucumã almond ( Astrocaryum vulgare ) (2.46%, n = 3) [ 35 ]; macadamia nut ( Macadamia spp.) (1.64%, n = 2) [ 54 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall acceptability score (6.63) obtained after 10 days of refrigerated storage was very good since the product is new and also it does not have any additional sugar and flavorings; it is just a natural product. Therefore, it could be concluded that the beverage was accepted by the consumers after 10 days of refrigerated storage since its overall acceptability score was 6.63, which is in the acceptable range of 6 (like slightly) to 9 (like moderately) (Lima et al, 2020). Nearly similar overall acceptability score of 6.8 has been reported by Aparicio‐García et al (2021) for sprouted oat fermented beverage.…”
Section: Resultsmentioning
confidence: 99%